Cardiac‐specific succinate dehydrogenase deficiency in Barth syndrome - Jan Dudek; I‐Fen Cheng; Arpita Chowdhury; Katharina Wozny; Martina Balleininger; Robert Reinhold; Silke Grunau; Sylvie Callegari; Karl Toischer; Ronald JA Wanders; Gerd Hasenfuß; Britta Brügger; et al. (EMBO Molecular Medicine)
Abstract Barth syndrome (BTHS) is a cardiomyopathy caused by the loss of tafazzin, a mitochondrial acyltransferase involved in the maturation of the glycerophospholipid cardiolipin. It has remained enigmatic as to why a systemic loss of cardiolipin leads to cardiomyopathy. Using a genetic ablation of tafazzin function in the BTHS mouse model, we identified severe structural changes in respiratory chain supercomplexes at a pre‐onset stage of the disease. This reorganization of supercomplexes was specific to cardiac tissue and could be recapitulated in cardiomyocytes derived from BTHS patients. Moreover, our analyses demonstrate a cardiac‐specific loss of succinate dehydrogenase (SDH), an enzyme linking the respiratory chain with the tricarboxylic acid cycle. As a similar defect of SDH is apparent in patient cell‐derived cardiomyocytes, we conclude that these defects represent a molecular basis for the cardiac pathology in Barth syndrome.